Are Hypometric Anticipatory Postural Adjustments Contributing to Freezing of Gait in Parkinson’s Disease? - Schlenstedt, Christian; Mancini, Martina; Nutt, Jay; Hiller, Amie P.; Maetzler, Walter; Deuschl, Günther; Horak, Fay (Frontiers in Aging Neuroscience, 2018)
Introduction: This study aims at investigating whether impaired anticipatory postural adjustments (APA) during gait initiation contribute to the occurrence of freezing of gait (FOG) or whether altered APAs compensate for FOG in Parkinson's disease (PD). Methods: Gait initiation after 30 sec quiet stance was analyzed without and with a cognitive dual task (DT) in 33 PD subjects with FOG (PD+FOG), 30 PD subjects without FOG (PD-FOG) and 32 healthy controls (HC). APAs were characterized with inertial sensors and muscle activity of the tensor fasciae latae (TFL), gastrocnemius and tibialis anterior was captured with EMG recordings. Nine trials (of 190) were associated with start hesitation/FOG and analyzed separately. Results: PD+FOG and PD-FOG did not differ in disease duration, disease severity, age or gender. PD+FOG had significantly smaller medio-lateral (ML) and anterio-posterior APAs compared to PD-FOG (DT, p<0.05). PD+FOG had more co-contraction of left and right TFL during APAs compared to PD-FOG (p<0.01). Within the PD+FOG, the ML size of APA (DT) was positively correlated with the severity of FOG history (NFOG-Q), with larger APAs associated with worse FOG (rho=0.477, p=0.025). ML APAs were larger during trials with observed FOG compared to trials of PD+FOG without FOG. Conclusions: People with PD who have a history of FOG have smaller ML APAs (weight shifting) during gait initiation compared to PD-FOG and HC. However, start hesitation (FOG) is not caused by an inability to sufficiently displace the center of mass towards the stance leg because APAs were larger during trials with observed FOG. We speculate that reducing the acceleration of the body center of mass with hip abductor co-contraction for APAs might be a compensatory strategy in PD+FOG, to address postural control deficits and enable step initiation.